Growth Characteristic and Conditioning Factors of Mackerel Fish (Scomberomorus commersonii) Landed at PPI Cikidang Pangandaran West Java - Muhammad Gianaya Adinalda; Dyahruri Sanjayasari (Fakultas Perikanan dan Ilmu Kelautan, 2022)
Mackerel fish (Scomberomorus commersonii) is one of potential catch in Indonesia. The production of mackerel fish in Indonesia has become the highest in the world exceeding the Philippines, Cingalese, Yemen, and Pakistan. Currently, mackerel fish is used maximumly by considering its sustainability. Present study aimed to understand the growth characteristic and condition factors for mackerel fish which landed at PPI Cikidang, Pangandaran, West Java. The data was collected at PPI Cikidang, Pangandaran, West Java in February 2021. Survey and observation method were used to obtain the growth characteristic of mackerel fish, and it analyzed descriptively. The results of the study revealed that the growth of mackerel fish landed at PPI Cikidang Pangandaran was allometric negative with the b value at 1.71. The growth characteristic based on length-weight relation showed strong relationship with coefficient determination at 93.1%. The condition factor resulted 0.64 with average of relative weight 100.75. The regression relationship between relative weight and condition factors had weak relationship.